Synthesis, in-vitro antimicrobial and antitubercular screening of Schiff bases of 3-amino-1-phenyl-4- [2-(4-phenyl-1,3-thiazol-2-yl) hydrazin-1-ylidene]-4,5-dihydro-1H-pyrazol-5-one - K K Sivakumar; A Rajasekaran (Wolters Kluwer Medknow Publications, 2013)
Purpose: Synthesis and antimicrobial activity of some Schiff bases of 3-amino-1-phenyl-4- [2-(4-phenyl-1,3-thiazol-2-yl) hydrazin-1-ylidene]-4,5-dihydro-1H-pyrazol-5-ones (TZP4a-l) are described. Materials and Methods: Structures of the synthesized compounds were confirmed using infrared, 1 H nuclear magnetic resonance, and mass spectral data. Synthesized compounds were tested in-vitro against four Gram-positive and four Gram-negative bacterial strains, three fungal strains and two mycobacterial strains. Title compounds were screened its in-vitro cytotoxicity (IC 50 ) by 3-(4,5-dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay using mouse embryonic fibroblasts cell line (NIH 3T3). Results and Discussion: Compounds TZP4 g and TZP4 h were found to be significant activity against Bacillus substilis (bacteria) and Aspergillus niger (fungi). In-vitro anti-tuberculosis (TB) activity of compound TZP4g showed appreciable antitubercular activity against Mycobacterium tuberculosis H37Rv strain (minimum inhibitory concentration [MIC] =0.6.48 × 10−3 μM/mL) which was 1.69 and 3.91 times more active than the standard drug, pyrazinamide (25.38 × 10−3 μM/mL) and streptomycin (MIC = 11.01 × 10−3 μM/mL), respectively. Their in-vitro cytotoxicity (IC 50 ) was determined to establish a selectivity index (SI) (SI = IC 50 /MIC). Compounds TZP4 c, TZP4 g, and TZP4 h have SI 82.85, 168.88, and 199.07, respectively. Conclusion: All the title compounds had mild toxicity on the mouse embryonic fibroblasts NIH 3T3 cells (IC 50 ≥ 100 μM). In comparison to the results of toxicity and antimycobacterial activity tests, it was observed that the activity of the compounds is not due to general toxicity effect; however, their antimycobacterial activity can be possibly because of their selective antimycobacterial effect. We concluded from our investigations that TZP4 c, TZP4 g, and TZP4 h may be considered promising for the development of new anti-TB agents.